Maculopapular cutaneous Mastocytosis - Pinho,Crisbety (2022)
Abstract Mastocytosis is a rare disorder caused by proliferation and accumulation of mast cells in various tissues, with characteristic symptoms associated with the release of their mediators. Its cutaneous form, usually benign, is the most frequent among children. The authors report the case of a two-month-old male infant who presented to the Emergency Department with small, tan-to-brown macules and papules distributed mainly on the trunk, which progressively became nodular and bullous, with one month of evolution. Darier´s sign was positive. The absence of systemic signs and analytic (including serum tryptase level) and echographic changes was consistent with the diagnosis of maculopapular cutaneous mastocytosis, or urticaria pigmentosa, subsequently confirmed by skin biopsy. Treatment with anti-histaminic therapy and topical immunosuppressant and avoidance of triggering factors led to a positive outcome.